The Effect Of Baby Massage On Weight Gain In Infants Aged 1-6 Months At The Sumartini Maternity And Child Health Clinic In 2026 - Ika Wijaya; Nova Rati Lova; Maulida Lathifah (Public Health Journal, 2026)
The 1- to 6 month age period is a phase of rapid growth for infants, making it necessary to monitor their weight changes regularly. Weight can serve as one parameter for assessing an infant’s growth and overall condition. Weight gain does not always proceed optimally for every infant, so stimulation is needed to support the growth process. One form of stimulation that can be applied to infants is baby massage. Massage through touch can help create a comfortable environment while supporting physiological processes related to the infant’s digestion and growth. This study aims “to determine the effect of baby massage on weight gain in infants aged 1-6 months at the Sumartini Midwife’s TPMB in 2026.” This is a quantitative study using a pre-experimental design that implements a one-group pretest-posttest approach. The study sample consisted of 32 infants aged 1-6 months selected through purposive sampling. Weight measurements were taken before and after baby massage sessions lasting 10-15 minutes, conducted twice a week. Data analysis was performed using the Wilcoxon Signed-Rank Test. The findings confirmed that before the baby massage, 21 infants (65.6%) were in the underweight category and 11 infants (34.4%) were in the normal category. After the baby massage, 31 infants (96.9%) were in the normal weight category and 1 infant (3.1%) was in the underweight category. The average weight increased from 5,018 grams before the intervention to 5,618 grams after the intervention, with an average increase of 600 grams. The results of the Wilcoxon test indicated a significant effect of baby massage on infants’ weight gain (p < 0.001). Therefore, it can be concluded that “baby massage has an effect on weight gain in infants aged 1-6 months at the Sumartini Midwife’s TPMB